콘크리트 및 복합재료용 멀티스케일 가상 시험기계에 관한 소고 - Bezawit F. Haile; 박솔뫼; 양범주; 이행기 (한국전산구조공학회, 2018)
Recently composite materials have dominated most engineering fields, owing to their better performance, increased durability and flexibility to be customized and designed for a specific required property. This has given them unprecedented superiority over conventional materials. With the help of the ever increasing computational capabilities of computers, researchers have been trying to develop accurate material models for the complex and integrated properties of these composites. This has led to advances in virtual testing of composite materials as a supplement or a possible replacement of laboratory experiments to predict the properties and responses of composite materials and structures. This paper presents a review on the complex multi-scale modelling framework of the virtual testing machines, which involve computational mechanics at various length-scales starting with nano-mechanics and ending in structure level computational mechanics, with a homogenization technique used to link the different length scales. In addition, the paper presents the features of some of the biggest integrated virtual testing machines developed for study of concrete, including a multiscale modeling scheme for the simulation of the constitutive properties of nanocomposites. Finally, the current challenges and future development potentials for virtual test machines are discussed.